Revision of the Papua New Guinean fig wasp genus Robertsia Boucek (Hymenoptera: Chalcidoidea: Pteromalidae: Sycoecinae) - van Noort, Simon; Rasplus, Jean-Yves (Zootaxa, 2005)
Two new species of Robertsia, R. weibleni and R. vaamondei are described from Papua New Guinea. Four species of Robertsia are now known from a single host fig tree species, Ficus xylosycia. Illustrations and keys are provided for both sexes of all four species. An online key is available at: http://www.figweb.org/Fig_wasps/Pteromalidae/Sycoecinae/Key/Robertsia.htm. Host relationships and biology are discussed.